Pengaruh Persepsi Keamanan Web dan Kesesuaian Lifestyle terhadap Minat Penggunaan Internet Banking: Technology Acceptance Model yang Dimodifikasi - Fitria Magdalena Suprapto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this research is to examine factors that influence attitude and intention to use internet banking with theoretical model of Technology Acceptance Model (TAM) developed by Davis (1989) and development model used by Cheng et al. (2006) and Cho (2005). The antecedent of intention of using in this study are usefulness, ease of use, web security, lifestyle compatibility, and attitude. Although internet banking offers many benefits, people are not interested to use that. This research proves that the attitude in adopting internet banking is determined by the perceived usefulness, web security, and lifestyle compatibility. Whereas perceived ease of use does not effect the attitude of using internet banking. The implication of this research is to provide a reference to improve and enhance the quality of online services, especially internet banking facility in accordance with customers’ demands for customer satisfaction and loyalty. In this study, perceived usefulness has the most dominant effect to attitude and intention of using internet banking. Keywords: Technology Acceptance Model (TAM), internet banking, behavioral intention, attitude towards behavior, perceived usefulness, ease of use, web security, compatibility.